MT-Nanotubes: Lifelines for Stem Cells. - Amoyel, M.; Bach, E.A. (Cell Stem Cell, 2015)
Niche cells produce secreted factors that promote the self-renewal of stem cells in their immediate proximity, but how signaling is restricted to stem cells is not well understood. Inaba et al. (2015) report that microtubule (MT) structures called MT-nanotubes control activation of the primary self-renewal pathway in Drosophila testes.